Genome editing tools : a brief overview - Mudziwapasi, Reagan (London: CRC Press, 2022)
"This book succinctly reviews and describes genome editing tools such as ZFNs, CRISPR, megaTALs and TALENs. It covers the history, principles, applications and the advantages and disadvantages of each tool. The book provides an approachable outline enhancing science education in schools and universities by demystifying genome editing technologies"--
Includes bibliographical references and index.
Keywords: Gene editing; Genetics